Activation of neuronal FLT3 promotes exaggerated sensorial and emotional pain-related behaviors facilitating the transition from acute to chronic pain. (March 2023) - Tassou, Adrien; Thouaye, Maxime; Gilabert, Damien; Jouvenel, Antoine; Leyris, Jean-Philippe; Sonrier, Corinne; Diouloufet, Lucie; Mechaly, Ilana; Mallié, Sylvie; Bertin, Juliette; Chentouf, Myriam; Neiveyans, Madeline; et al.
Abstract: Acute pain has been associated with persistent pain sensitization of nociceptive pathways increasing the risk of transition from acute to chronic pain. We demonstrated the critical role of the FLT3- tyrosine kinase receptor, expressed in sensory neurons, in pain chronification after peripheral nerve injury. However, it is unclear whether injury-induced pain sensitization can also promote long-term mood disorders. Here, we evaluated the emotional and sensorial components of pain after a single (SI) or double paw incision (DI) and the implication of FLT3. DI mice showed an anxiodepressive-like phenotype associated with extended mechanical pain hypersensitivity and spontaneous pain when compared to SI mice. Behavioral exaggeration was associated with peripheral and spinal changes including increased microglia activation after DI versus SI. Intrathecal microglial inhibitors not only eliminated the exaggerated pain hypersensitivity produced by DI but also prevented anxiodepressive-related behaviors. Behavioral and cellular changes produced by DI were blocked in Flt3 knock-out animals and recapitulated by repeated intrathecal FL injections in naive animals. Finally, humanized antibodies against FLT3 reduced DI-induced behavioral and microglia changes. Altogether our results show that the repetition of peripheral lesions facilitate not only exaggerated nociceptive behaviors but also induced anxiodepressive disorders supported by spinal central changes that can be blocked by targeting peripheral FLT3. Highlights: Understanding the transition from acute to chronic pain remains an unmet challenge. Repeated peripheral acute injuries induce exaggerated pain-related behaviors including anxiodepression. Repeated peripheral injuries and FLT3 activation increases spinal microgliosis. Flt3 deletion or humanized antibody against FLT3 blocks repeated acute injuries-induced behavioral alterations and spinal microgliosis. Neuronal FLT3 plays a key role in the transition from acute to chronic pain.